Monensin Sensitive 1 Regulates Dendritic Arborization in Drosophila by Modulating Endocytic Flux - Harish, Rohit Krishnan; Tendulkar, Shweta; Deivasigamani, Senthilkumar; Ratnaparkhi, Anuradha; Ratnaparkhi, Girish S. (Frontiers in Cell and Developmental Biology, 2019)
Monensin Sensitive 1 (Mon1) is a component of the Mon1:Ccz1 complex that mediates Rab5 to Rab7 conversion in eukaryotic cells by serving as a guanine nucleotide exchange factor for Rab7 during vesicular trafficking. We find that Mon1 activity modulates the complexity of Class IV dendritic arborization (da) neurons during larval development. Loss of Mon1 function leads to an increase in arborization and complexity, while increased expression, leads to reduced arborization. The ability of Mon1 to influence dendritic development is possibly a function of its interactions with Rab family GTPases that are central players in vesicular trafficking. Earlier, these GTPases, specifically Rab1, Rab5, Rab10, and Rab11 have been shown to regulate dendritic arborization. We have conducted genetic epistasis experiments, by modulating the activity of Rab5, Rab7, and Rab11 in da neurons, in Mon1 mutants, and demonstrate that the ability of Mon1 to regulate arborization is possibly due to its effect on the recycling pathway. Dendritic branching is critical for proper connectivity and physiological function of the neuron. An understanding of regulatory elements, such as Mon1, as demonstrated in our study, is essential to understand neuronal function.